Active Learning Approach for Python Programming - Namratha, M.; Rekha, G. S.; Akram, Syed; Selva Kumar, S.; Nayak, Jyothi S. (Journal of Engineering Education Transformations, 2018)
In Outcome-Based Education, Active Learning methodology is used to improve the learning of the students in the classroom. To enhance the project implementation skill of the students, one of the Comprehensive Courses was introduced namely "Programming in Python" for the undergraduate students of Department of Computer Science & Engineering. In this course, students carry out a project on the concepts learned during the course. Active learning introduced in this course, helped the students to engage in the implementation of projects, weekly reviews, and discussion with peers to implement the concepts learned in the classroom. The active learning framework helped the faculties to review and evaluate the project work. The outcome of active learning helped the students to solve the problems with project techniques than learning programming construct.